En manlig identitet med kvinnliga drag - G. Olsson, Claes (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2002)
The article poses the question of what effect childhood experiences of male and female role models have on the choice of profession and on gender identity. For a man to choose a female-dominated profession can be considered a crossing of established gender boundaries. It does not, however, necessarily imply a politically conscious attempt to change prevailing gender patterns. Rather, it is about choosing an environment where one’s gender identity can develop on its own terms in an interwoven blend of masculinity and femininity.